The influence of gender and traumatic experiences on length of time served in juvenile justice settings - Espinosa, Erin M. (Criminal justice and behavior, 2016)
This study examines the influence of gender and history of trauma exposure on the length of time juvenile offenders served in post-adjudicatory placements. Data were drawn from a database that included information on all juvenile referrals from three large urban counties in Texas during a 2-year period. The study sample included all juveniles (N = 5,019) placed in local non-secure and county-operated secure facilities. Findings indicate that female juveniles served significantly longer periods of confinement in local facilities than boys, even when controlling for other influential variables such as offense severity, prior record, age at referral, and facility type. Findings also indicate that girls with histories of trauma served longer periods in confinement than boys for violating their court-ordered conditions of probation.